Experimental investigation into the effects of flat plate guiding walls on the performance of vertical axis wind turbine - Roaa Ansaf,; Mohamed Mohamed Elsakka,; Khaled Almohammadi,; Ahmed Fazlizan,; Mohammad Rasidi Rasani,; Zambri Harun, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Vertical axis wind turbines (VAWTs) are expected to have good market potential soon. However, it suffers from relatively lower performance in contrast with the market-leading horizontal axis wind turbine (HAWT). To overcome the disadvantages of VAWTs and improve their performance, this study aims to experimentally investigate the effect of flat plate guiding walls on the performance of VAWTS. The experimental study was carried out in an open-jet wind tunnel with an airflow speed range between 8 - 12 m/s and a different tip speed ratio (TSR). The rotor is of NACA0021 with three blades, 50 mm length, 300 mm diameter and 300 mm height. The guiding wall row is composed of six flat plates. The results show that a straight-bladed vertical axis wind turbine surrounded by guiding walls could be self-starting at the wind velocity of 4 m/s which is lower than the wind speed required for the turbine without guiding plates is about 5 m/s. The rotational speed increases for all test conditions with the increase in wind velocity. The power coefficient (Cp) increases with TSR (λ) until reaching its peak at experimental results for all tests. The power coefficient of the turbine reaches its highest value Cp = 0.25 at λ = 1.79 at 12 m/s with the guiding walls. The optimal Cp using the fixed guiding walls shows about 23% improvement at 8 m/s in contrast with the optimal Cp of the reference turbine without the guiding walls.